Analisis Kemampuan Berpikir Kritis Siswa dalam Menyelesaikan Masalah Matematika Berbasis Etnomatematika - Hari, Ayutia Khoirotul; Putra, Eric Dwi; Sujiwo, Dimas Anditha (Media Pendidikan Matematika, 2025)
Mathematics is one of the branches of science that continues to develop to meet human and technological needs. This means that students must improve their ability to think systematically, analytically, logically, critically, and creatively. The main problem in this study is how to describe students' critical thinking skills in solving math problems through the ethnomathematics approach. The purpose of this study is to describe students' critical thinking skills in solving math problems using the ethnomathematics approach, which combines mathematical materials with their local culture. This research uses a qualitative descriptive approach with research instruments in the form of tests and interviews involving data analysis from interviews and test answers.Â  The results showed that high ability students (KT1 and KT2) met all four indicators, namely interpretation, analysis, evaluation, and inference. Students with low ability (KR1 and KR2) only fulfill two indicators, namely analysis and interpretation. This study also shows that the traditional game of dam-daman is effective in describing students' mathematical ability to think critically. To help low-ability students fulfill all critical thinking criteria, further research is needed.